Epidemiology and Diagnosis of Hepatitis B in the Mediterranean Region and Elsewhere - EREN, FATİH (SPRINGER, 2010)
After cancer, viral infections constitute a great threat to human health throughout the world and among these viral hepatitis constitutes one of the most important public threats in the world. Despite considerable advances in medical technology and attempts to eradicate the diseases, viral hepatitis still remain as major public health problem with their high morbidity and mortality in the Mediterranean, Eastern Europe, Middle East and elsewhere. Uncontrolled migratory flow from developing countries to regions of low endemicity gave rise to changes not only in the prevalence of viral infection but also the genotype, clinical course and modes of transmission. Among several viruses which may affect the liver those which constitute important public health problems are hepatitis A, B, C, D, and E. All of these viruses can cause an acute disease with symptoms lasting several weeks however HBV can cause asymptomatic infection which can silently progress to chronic infection in which the patient never gets rid of the virus and many years later develops cirrhosis of the liver or liver cancer. Of the two billion people who have been infected with HBV, more than 350 million have chronic (lifelong) infections. In this chapter, we reviewed the present situation, epidemiology, clinical presentation, prevention, diagnostic techniques and the universal importance of Hepatitis B.
Keywords: Hepatitis B infection; hepatocellular carcinoma, cirrhosis; epidemiology; HBV; REAL-TIME PCR; SURFACE-ANTIGEN HBSAG; C VIRUS-INFECTIONS; HBV MONITOR TEST; NATURAL-HISTORY; DISEASE PROGRESSION; CURRENT PREVALENCE; UNSAFE INJECTIONS; HYPERENDEMIC AREA; DEVELOPING-WORLD